DOP22 Antibiotic Use as a Risk Factor for Inflammatory Bowel Disease Across the Ages: A Population-Based Cohort Study. (30th January 2023) - Faye, A; Allin, K; Iversen, A; Agrawal, M; Faith, J; Colombel, J F; Jess, T
Abstract: Background: There is an increasing incidence of inflammatory bowel disease (IBD) for which environmental factors are suspected. Antibiotics have been associated with development of IBD in earlier generations, but their influence on IBD risk across the ages is uncertain. We assessed the changing impact of antibiotic exposure, including dose response, timing, and antibiotic class, on the risk of IBD in all individuals ≥10 years-old. Methods: Using Denmark nationwide registries, a population-based cohort of residents ≥10 years-of-age was established between 2000 and 2018. Incidence rate ratios (IRRs) for IBD following antibiotic exposure were calculated using Poisson regression, with adjustment for concomitant PPI, antiviral and antifungal use. Results: There were a total of 6, 104, 245 individuals, resulting in 87, 112, 328 person-years of follow-up, 36, 017 new cases of ulcerative colitis (UC) and 16, 881 new cases of Crohn's disease (CD). Antibiotic exposure was associated with an increased risk of IBD as compared with no antibiotic exposure for all age groups, though was greatest among individuals aged 40-60 years-old and ≥ 60 years-old (10-40 years-old, IRR 1.28, 95%CI 1.25-1.32; age 40-60 years-old, IRR 1.48, 95%CI 1.43-1.54; age ≥ 60 years-old, IRR 1.47, 95%CI 1.42-1.53). When assessing the number of antibiotic courses received, each subsequent course added additional risk, leading to a positive dose response relationship for all age groups: increase in IRR per antibiotic course was 1.11 (95% CI 1.10-1.12), 1.15 (95% CI 1.14-1.16), and 1.14 (95% CI 1.13-1.15) for individuals aged 10-40 years, 40-60 years, and ≥60 years, with similar results seen for both UC and CD. The highest risk of developing IBD was observed 1-2 years after antibiotic exposure, and after use of antibiotic classes often prescribed to treat gastrointestinal pathogens. Nitrofurantoin, which has minimal impact on the intestinal microbiome, was not associated with risk of IBD across all age groups (age 10-40 years IRR 1.11, 95%CI 0.88-1.38; age 40-60 years IRR 1.22 (95%CI 0.95-1.53); age ≥60 years IRR 0.93, 95%CI 0.79-1.07). Conclusion: Our results demonstrate a positive dose response, highlighting the strong association between antibiotic exposure and the development IBD, particularly among adults forty years and older. This risk was highest in the years immediately following antibiotic use, persisted across antibiotic classes impacting the gastrointestinal microbiome, and was associated with the development of both UC and CD. Thus, antibiotic stewardship may be important not only to limit the development of multidrug resistant organisms, but also to reduce the risk of IBD, particularly among older adults.